Expressive Speech Acts in Cross-Cultural Communication: A Pragmatic Analysis of Lost in Translation Film - Amalia, Siti Nur; Rohali, Rohali; Andriyanti, Erna (Universitas Ahmad Dahlan, 2025)
This research investigates expressive spech acts in intercultural communication as depicted in the film Lost in translation. Focusing on complimenting, critiquing, appreciating, apologising, and expressing confusion, the study draws on Searle’s theory of expressive speech acts, Brown and Levinson’s politeness theory, and Hofstede’s cultural dimensions – particularly individualism and collectivism. Using a qualitative descriptive method, the researcher analyses interactions between American and Japanese characters, exploring how emotions and social intentions between American and Japanese characters, exploring how emotions and social intentions are conveyed acroos cultures. The study finds that American reflecting individualist values, tend to communicate emotions directly, using strategies that promote validation and closeness. Conversely, Japanese speakers, shaped by collectivist norms, prefer indirect, polite speech that priorities harmony and social etiquette. These contrasting pragmaticpoliteness strategies reveal the need for balance and adaptability in intercultural communication. The findings suggest that expressive speech acts are deeply embedded in cultural and social hierarchies, and misinterpretation may lead to misunderstandings or conflicts. The research also highlights the role of the film as a medium for observing authentic communication within a controlled context. Ultimately, the study underlines the importance of pragmatic sensitivity in a globalised world and calls for more research in cross-cultural pragmatics to foster effective and respectful Intercultural interactions.